2017
DOI: 10.1016/j.fertnstert.2017.10.035
|View full text |Cite|
|
Sign up to set email alerts
|

Obstetrical complications of endometriosis, particularly deep endometriosis

Abstract: Over the past few years, a new topic in the field of endometriosis has emerged: the potential impact of the disease on pregnancy outcomes. This review aims to summarize in detail the available evidence on the relationship between endometriosis, particularly deep endometriosis (DE), and obstetrical outcomes. Acute complications of DE, such as spontaneous hemoperitoneum, bowel perforation, and uterine rupture, may occur during pregnancy. Although these events represent life-threatening conditions, they are rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 120 publications
(168 reference statements)
3
32
0
3
Order By: Relevance
“…We found an increased incidence of caesarean sections in the case group compared to controls, mainly performed in elective regimen. Several meta-analyses and reviews found a correlation between endometriosis and caesarean section [29,34]. In a study performed by Maggiore et al, the main indication for caesarean section in women with endometriosis was fetal distress, followed by breech presentation and dystocia [26].…”
Section: Discussionmentioning
confidence: 99%
“…We found an increased incidence of caesarean sections in the case group compared to controls, mainly performed in elective regimen. Several meta-analyses and reviews found a correlation between endometriosis and caesarean section [29,34]. In a study performed by Maggiore et al, the main indication for caesarean section in women with endometriosis was fetal distress, followed by breech presentation and dystocia [26].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] However, two interesting and comprehensive reviews by Leone Roberti Maggiore et al have highlighted that the risk of complications associated with endometriosis during pregnancy is low. 23,24 While the available literature suggests that there is an increased risk of placenta previa, particularly in patients with deep endometriosis, pregnant women with endometriosis should be in general reassured regarding the course of their gestation. Few studies, however, have focused on the possible similarities and differences among the different types and locations of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, a nonnegligible increase in the likelihood of placenta accrete, preterm birth, and aesarean delivery has been described. [23][24][25][26] Unfortunately, most of the available evidence relies either on population-based studies, which used codes of the diagnoses for both the mother and the newborn at the time of discharge from the hospital, or on small retrospective collections of data with conflicting results. Moreover, attention has been given almost exclusively to pregnancy and maternal outcomes, whereas scant data are available on the neonates.…”
mentioning
confidence: 99%
“…Saraswat et al compared late pregnancy outcomes in 4232 women with endometriosis and 6707 without endometriosis and reported that the rate of placenta previa was 1.7% in the former group and 0.8% in the latter (adjusted odds ratio, 2.2; 95% CI, 1.5-3.3) [16,17]. Other studies have also reported that the incidence of placenta previa is high in patients with endometriosis [4,5,18]; thus, the frequency at which obstetricians encounter placenta previa or PAS may increase with an increase in the incidence of endometriosis.…”
Section: Discussionmentioning
confidence: 99%